A Review of the Aetiopathogenesis and Clinical and Histopathological Features of Oral Mucosal Melanoma - Liviu Feller; Razia A. G. Khammissa; Johan Lemmer (The Scientific World Journal, 2017)
Oral mucosal melanoma is an uncommon, usually heavily melanin-pigmented, but occasionally amelanotic aggressive tumour with a poor prognosis. Despite radical surgery, radiotherapy, or chemotherapy, local recurrence and distant metastasis are frequent. Microscopical examination is essential for diagnosis, and routine histological staining must be supplemented by immunohistochemical studies. The aetiology is unknown, the pathogenesis is poorly understood, and the 5-year survival rate rarely exceeds 30%. In most cases, oral mucosal melanoma arises from epithelial melanocytes in the basal layer of the epithelium and less frequently from immature melanocytes arrested in the lamina propria. In both cases the melanocytes undergo malignant transformation, invade deeper tissues, and metastasize to regional lymph nodes and to distant sites. Very rarely metastasis from skin melanoma may give rise to oral mucosal melanoma that may be mistaken for primary oral mucosal melanoma. The pathogenesis of oral mucosal melanoma is complex involving multiple interactions between cytogenetic factors including dysregulation of the cKit signalling pathways, cell cycle, apoptosis, and cell-to-cell interactions on the one hand and melanin itself, melanin intermediates, and local microenvironmental agents regulating melanogenesis on the other hand. The detailed mechanisms that initiate the malignant transformation of oral melanocytes and thereafter sustain and promote the process of melanomagenesis are unknown.